Fourier transform Infrared Spectroscopy and Thermogravimetric analysis of a Siddha Herbomineral formulation Kandhaga Rasayanam - MEENA .R; RAMASWAMY.R.S (International Journal of Pharma and Bio Sciences, 2018)
Siddha system of medicine is one of the oldest traditional systems originated from Tamil Nadu. The Siddha herbomineral drug Kandhaga Rasayanam is chosen from classic Siddha text Siddha Vaithya Thirattu.Kandhagam is the sole mineral ingredient in the formulation.Withania somnifera Dunal,Smilax china Linn,. Terminalia chebula Retz.,Phyllanthus emblica Linn.,Terminalia bellerica Roxb.,Zingiber officinale Roscoe , Piper longum Linn.,Piper nigrum Linn.,Embelia ribes Burm,Elataria cardamomum Linn.,Cinnamomum zeylanicum Breyn,Santalum album Linn.,Cicer arietinum Linn.,Semecarpus anacardium.Linn , Plumbago zeylanica.Linn., are the herbal ingredients.The raw drugs are purified and the formulation was as per the methods described in literature.It is indicated for various type of arthritis, venereal diseases, urinary infections, skin infections, etc.; Standardisation of Siddha drugs is the need of the hour. Physicochemical analysis,HPTLC studies, acute and long term toxicity of Kandhaga Rasayanam are already published.The aim of the present study is to characterize the Siddha formulation Kandhaga Rasayanam using Fourier Transform Infra Red Spectroscopy (FT-IR)and Thermogravimetric Analysis (TGA). FT-IR spectra was recorded using a Fourier Transform Infrared spectrometer, model FTIR- 6300, JASCO International Company, Japan.The FT-IR spectroscopy applied in the mid infra-red region 4000 cm-1 to 400 cm-1 revealed the presence of O-C=O bending, -CH2 out of plane, -CN stretching, -COO stretching in carboxylic, -CH2 in aliphatic compounds, =CH in aromatic compounds, -OH stretching etc. Thermal properties of the drug sample were investigated on a Thermo Gravity instrument Q-500 model. At 910ºC,4.640 % of the drug was disintegrated.The FTIR analysis and TGA has showed various aliphatic, aromatic and saturated compounds. Kandhaga Rasayanam is a heat stable herbomineral formulation profile. Further studies have to be carried out to standardize the formulation.